(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2020)
This article has no abstract. The first 100 words appear below: A 15-year-old boy 4th issue of a non-consanguineous parents presented with a history of multiple plaques and patches on the scalp, trunk, upper and lower extremities since birth. Initially, the plaques and patches were smaller in sizes, dark brown in color, painless and non-pruritic. Since 4th year of his age, these plaques start increasing in size and color turned into black gradually. The lesion on the scalp became a giant cerebriform plaque that involved left parietal region. Lesions on the trunk, upper and lower extremities became polysized and polyshaped hyperpigmented papules and nodules.